Transformation of Sharia Supervision in the Digital Islamic Financial Ecosystem: Challenges and National Policy Directions - Ermiati, Ermiati (Sekolah Tinggi Agama Islam Al-Furqan, Makassar - Indonesia, 2025)
The digital transformation in the Islamic finance industry presents complex challenges to the effectiveness of the Islamic supervisory system. This study aims to analyze the strategic role of the Islamic Supervisory Board (SSB) in the digital financial ecosystem and identify key challenges and policy directions needed to strengthen its supervisory function. The research uses a qualitative approach with descriptive methods and case studies based on secondary literature, encompassing national regulations, policy reports, and recent scientific articles. Key findings indicate that the SSB faces structural, regulatory, and technological constraints that impact its supervisory effectiveness, particularly in the face of developments in financial technology such as Islamic fintech and digital banking. The lack of specific regulations, low technological literacy among SSB members, and limited institutional capacity hinder adaptive supervisory integration. The study also highlights the importance of utilizing real-time audit technology and strengthening regulations based on the principles of maqasid sharia to support the sustainability of the digital Islamic financial system. The study's conclusions emphasize that strengthening Islamic supervision in the digital era requires regulatory reform, increased human resource capacity, and technology integration based on Islamic governance principles. This study has implications for policy design and the development of an innovative and sustainable Islamic supervisory system.